THE EFFECT OF SERVICE LEVEL BAITUL MAAL WAT-TAMWIL TUMANG ON MEMBER’S SATISFACTION OF MUDHARABAH DEPOSITS - Utami, Wikan Budi; Ningsih, Suhesti; Paidi, Paidi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
The purpose of this study was to determine the effect of service quality which includes compliance, assurance, reliability, tangible, empathy, and responsiveness to the satisfaction level of deposit members. mudaraba in KSPPS BMT Tumang Selo Branch. This study uses a quantitative descriptive approach with a population of mudharabah savings members in KSPPS BMT Tumang Selo Branch, the sample is taken using simple random sampling method. The data analysis is using multiple linear regression models. The results of this study indicate that the adjusted R square determination coefficient is 0.648. This shows that the independent variable is able to influence the dependent variable by 65%, while the remaining 35% is obtained by other variables outside this research. Based on the F test shows that the significance number is 0,000, this states that the independent variables together can affect the dependent variable. The percentage based on variable empathy t test and responsiveness have a significant positive effect on member satisfaction, while the variables of compliance, assurance, reliability and tangible have no significant effect on member satisfaction. Keywords: Service quality, member satisfaction and mudharabah savings.